Optimization of sample unit size for sampling stink bugs (Hemiptera: Pentatomidae) in soybean. (July 2022) - Ribeiro, Arthur V.; Aita, Rafael Carlesso; Pezzini, Daniela T.; DiFonzo, Christina D.; Hunt, Thomas E.; Knodel, Janet J.; Krupke, Christian H.; Marchi-Werle, Lia; Michel, Andrew P.; Seiter, Nicholas J.; Wright, Robert J.; Hutchison, William D.; et al.
Abstract: Cost-effective and reliable sampling procedures are crucial for integrated pest management. Sweep net sampling is commonly used for stink bugs (Hemiptera: Pentatomidae) in soybean, with sample size being the number of sets of sweeps, and sample unit size the number of sweeps in each set. Sample unit size has received little attention, but can affect sampling parameters. Here, two sample unit sizes (10 vs. 25 sweeps) were compared for the sampling of stink bug taxa. On average, sampling for stink bugs took 3.6 more minutes with the 25-sweep than with the 10-sweep sample unit size. Generally, estimates of the mean number of stink bugs per sweep were similar between the two sample unit sizes for Euschistus spp. and Chinavia hilaris combined ("combined herbivores") and Euschistus spp. The 25-sweep sample unit size had a higher probability of detecting combined herbivores, Euschistus spp. and Podisus spp., lower standard errors and relative variance for combined herbivores and Euschistus spp., lower standard errors for C. hilaris, and higher relative net precision [which accounts for sampling cost (i.e., time)] for combined herbivores and Euschistus spp. Taken together, the better probability of detection, precision and efficiency of the 25-sweep sample unit size support the continued use of sampling plans developed for that sample unit size. The optimization of sample unit sizes is an important factor that should be accounted for in the development of sampling plans. Highlights: Two sample unit sizes (10 vs. 25 sweeps) were compared for sampling of stink bug taxa. Probability of detection, precision and efficiency were higher with 25 sweeps. Sample unit sizes should be evaluated when implementing sampling plans.